Impact of physical exercise on low back pain: a review - Sośniak, Izabella; Miejska-Kamińska, Marta; Jurczenko, Lidia (Journal of Education, Health and Sport, 2025)
Low back pain (LBP) is one of the most common musculoskeletal disorders, affecting up to 80% of the population at least once in their lifetime. As the leading cause of disability worldwide, LBP significantly impacts quality of life and functional ability. Due to the limited effectiveness of pharmacological treatments, there is growing interest in non-pharmacological therapies, particularly physical exercise. The aim of this review was to analyze the effectiveness of various forms of physical activity in the treatment of chronic non-specific low back pain (CNSLBP). The review considered stabilization training, core exercises, yoga, Pilates, breathing exercises, aquatic therapy, isokinetic training, dynamic neuromuscular stabilization (DNS), pelvic floor muscle training, and combined interventions, such as manual therapy with sexual counseling or group-based online programs. The results of the analyzed studies indicate that exercise—especially when individually tailored and comprehensive—is effective in reducing pain, improving function, and enhancing quality of life in patients with CNSLBP. Particularly beneficial outcomes were observed in programs that combined motor training with a psychosocial approach.